Modeling Alzheimer’s disease related phenotypes in the Ts65Dn mouse: impact of age on Aβ, Tau, pTau, NfL, and behavior - Overk, Cassia; Fiorini, Emma; Babolin, Chiara; Vukicevic, Marija; Morici, Catherine; Madani, Rime; Eligert, Valerie; Kosco-Vilbois, Marie; Roberts, Amanda; Becker, Ann; Pfeifer, Andrea; Mobley, William C. (Frontiers in Neuroscience, 2023)
People with DS are highly predisposed to Alzheimer's disease (AD) and demonstrate very similar clinical and pathological features. Ts65Dn mice are widely used and serve as the best-characterized animal model of DS. We undertook studies to characterize age-related changes for AD-relevant markers linked to Aβ, Tau, and phospho-Tau, axonal structure, inflammation, and behavior. We found age-related changes in both Ts65Dn and 2N mice. Relative to 2N mice, Ts65Dn mice showed consistent increases in Aβ40, insoluble phospho-Tau, and neurofilament light protein. These changes were correlated with deficits in learning and memory.